Properties and mechanisms of Z2-FET at variable temperature. (January 2016) - Dirani, Hassan El; Solaro, Yohann; Fonteneau, Pascal; Ferrari, Philippe; Cristoloveanu, Sorin
Abstract: This paper presents a systematic study of Z 2 -FET (Zero Subthreshold Swing and Zero Impact Ionization transistor) fabricated in advanced Fully Depleted Silicon On Insulator (FDSOI) 28 nm technology with Ultra-Thin Body and Buried Oxide (UTBB). It is a recent sharp-switching device that achieves remarkable performance in terms of leakage current and triggering control. The device features an extremely sharp on-switch, an adjustable triggering voltage ( V ON ), and is considered for Electro-Static Discharge (ESD) protection. The operation principle relies on the modulation of electrons and holes injection barriers. Experimental results show the effect of low and high temperature on the output characteristics, triggering voltage and leakage current.